Human nonvisual opsin 3 regulates pigmentation of epidermal melanocytes through functional interaction with melanocortin 1 receptor - Ozdeslik, Rana N. (Proc Natl Acad Sci U S A, 2019)
Opsins form a family of light-activated, retinal-dependent, G protein-coupled receptors (GPCRs) that serve a multitude of visual and nonvisual functions. Opsin 3 (OPN3 or encephalopsin), initially identified in the brain, remains one of the few members of the mammalian opsin family with unknown function and ambiguous light absorption properties. We recently discovered that OPN3 is highly expressed in human epidermal melanocytes (HEMs)—the skin cells that produce melanin. The melanin pigment is a critical defense against ultraviolet radiation (UVR), and its production is mediated by the Gαs-coupled melanocortin 1 receptor (MC1R). The physiological function and light sensitivity of OPN3 in melanocytes are yet to be determined. Here, we show that in HEMs, OPN3 acts as a negative regulator of melanin production by modulating the signaling of MC1R. OPN3 negatively regulates the cyclic adenosine monophosphate (cAMP) response evoked by MC1R via activation of the Gαi subunit of G proteins, thus decreasing cellular melanin levels. In addition to their functional relationship, OPN3 and MC1R colocalize at both the plasma membrane and in intracellular structures, and can form a physical complex. Remarkably, OPN3 can bind retinal, but does not mediate light-induced signaling in melanocytes. Our results identify a function for OPN3 in the regulation of the melanogenic pathway in epidermal melanocytes; we have revealed a light-independent function for the poorly characterized OPN3 and a pathway that greatly expands our understanding of melanocyte and skin physiology.